2011
DOI: 10.1159/000323616
|View full text |Cite
|
Sign up to set email alerts
|

Pars Plana Vitrectomy in Advanced Coats’ Disease

Abstract: Purpose: To report 5 cases of advanced Coats’ disease managed with pars plana vitrectomy and silicone oil tamponade. Methods: Five patients with advanced Coats’ disease and serous or tractional retinal detachment underwent pars plana vitrectomy with internal drainage, endolaser photocoagulation and silicone oil tamponade. One patient had combined phacoemulsification-vitrectomy surgery. Of the 5 patients, 1 had intravitreal hemorrhage and a retinal macrocyst and 1 had a retinal cyst. Follow-up period was 1–6 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…1,24,25,26 Additional internal or external subretinal fluid drainage also facilitates the application of laser photocoagulation or cryotherapy. Mutfuoglu ve Gulkilik 25 achieved positive anatomic and functional outcomes in 5 patients with PPV, internal subretinal fluid drainage and silicone oil tamponade. Despite postoperative anatomic success, functional success may be achieved in a small number of patients.…”
Section: Discussionmentioning
confidence: 99%
“…1,24,25,26 Additional internal or external subretinal fluid drainage also facilitates the application of laser photocoagulation or cryotherapy. Mutfuoglu ve Gulkilik 25 achieved positive anatomic and functional outcomes in 5 patients with PPV, internal subretinal fluid drainage and silicone oil tamponade. Despite postoperative anatomic success, functional success may be achieved in a small number of patients.…”
Section: Discussionmentioning
confidence: 99%
“…31 The latest studies have shown that the increasing use of anti-VEGF agents can also lead to a new application for the treatment of Coats disease. [32][33][34] The effect has been shown the raised VEGF level in aqueous humor and increases significantly as the disease prolongs. 35 The basic science behind the histopathologic review has depicted that macrophages in the subretinal space and which results in raised vascular permeability, in addition to this leads to angiogenesis due to increased expression of VEGF.…”
Section: Discussionmentioning
confidence: 99%
“…1 A retinal cyst without retinal detachment was noted in a case of Coats' disease. 2 We describe an idiopathic asymptomatic giant retinal cyst.…”
Section: Introductionmentioning
confidence: 96%